2023
DOI: 10.7717/peerj.16069
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of lipid accumulation index, triglyceride-glucose index and H-type hypertension and coronary artery disease

Wenwen Yuan,
Yan Shao,
Dong Zhao
et al.

Abstract: Objective The current research was designed to explore the relationship between the lipid accumulation index (LAP), coronary artery disease (CAD), and the triglyceride-glucose (TyG) index in patient with H-type hypertension. Methods From June 2021 to January 2022, our hospital’s information management system collected data on 186 patients with essential hypertension. The participants were categorized into two groups (H-type hypertension (n = 113) and non-H-type hypertension (n = 73)) based on their homocyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This is generally consistent with previous research findings, and if there are variations in influencing factors, they should be considered from the perspective of individual pathophysiology and lifestyle [ 25 , 26 ]. The study suggests that TG and LDL-C are independent variables influencing disease progression [ 27 ]. Meta-analysis results indicate that in the overall genetic model of the human population, individuals carrying the TT genotype have an increased risk of developing H-type hypertension [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is generally consistent with previous research findings, and if there are variations in influencing factors, they should be considered from the perspective of individual pathophysiology and lifestyle [ 25 , 26 ]. The study suggests that TG and LDL-C are independent variables influencing disease progression [ 27 ]. Meta-analysis results indicate that in the overall genetic model of the human population, individuals carrying the TT genotype have an increased risk of developing H-type hypertension [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately leads to the development of cardiovascular events, suggesting an association between HHcy and high TG (24). At the same time, a large number of epidemiological studies have shown that most hypertensive patients have dyslipidemia (25) and it has been demonstrated that lipid accumulation index (LAP) levels are higher in patients with H-type hypertension than in patients with non-H-type hypertension (26). Clinical observations have shown that hypertensive patients with elevated Hcy levels are positively associated with insulin resistance and diabetes mellitus (27)(28)(29), suggesting an association between FPG and H-type hypertension.…”
Section: Discussionmentioning
confidence: 99%